N=2 Susy Abelian Higgs Model with Hidden Sector and Bps Equations - Arias-Reyes, P (Springer Verlag, 2015)
Abstract: In this paper we study a system inspired on certain SUSY breaking models and on more recent Dark Matter scenarios. In our set-up, two Abelian gauge fields interact via an operator that mixes their kinetic terms. We find the extended Supersymmetric version of this system, that also generates a Higgs portal type of interaction. We obtain and study both analytically and numerically, the equations defining topologically stable string-like objects. We check our results using two different approaches. © 2015, The Author(s).